KELIMPAHAN MAKROZOOBENTHOS PADA TAMBAK TRADISONAL IKAN BANDENG (Chanos chanos) DI DESA SUNGAI UNDAN KECAMATAN RETEH KAB. INDRAGIRI HILIR - Kasma ruddin (Badan Perencanaan Pembangunan Daerah Kabupaten Indragiri Hilir Riau, 2017)
From the results of research macrozoobenthos abundance at each station looks different. The abundance of Marozobenthos differs on each station, where the highest abundance is Gastropoda class (45.87%), then Crustacea 31.13%, Bivalva 8.25%, Insecta (7.79%) and nematodes (5.96%). The average value of the highest diversity index lies on the pond surface (1.90), Outlet (1.65) and the lowest diversity index value lies in the caren (1.16), this condition indicates that the productivity is sufficiently balanced, to support the persecution of the cost due to the ecosystem condition that is balanced. Selanjutya The highest dominance index value on the surface of the pond (0.50), oulet (0.41) and the lowest in the caren (0.40).